Alignment of Nanoscale Single-Walled Carbon Nanotubes Strands - Yang, Danna; Wang, Lin; Zhang, Xiaoxian; Wang, Dongwei; Shen, Zhiqiang; Li, Sai (Nano-Micro Letters, 2011)
Depositing single-walled carbon nanotubes (SWNTs) with controllable density, pattern and orientation on electrodes presents a challenge in today’s research. Here, we report a novel solvent evaporation method to align SWNTs in patterns havingnanoscale width and micronscale length. SWNTs suspension has been introduced dropwise onto photoresist resin microchannels; and the capillary force can stretch and align SWNTs into strands with nanoscale width in the microchannels. Then these narrow and long aligned SWNTs patterns were successfully transferred to a pair of gold electrodes with different gaps to fabricate carbon nanotube field-effect transistor (CNTFET). Moreover, the electrical performance of the CNTFET show that the SWNTs strands can bridge different gaps and fabricate good electrical performance CNTFET with ON/OFF ratio around 106. This result suggests a promising and simple strategy for assembling well-aligned SWNTs into CNTFET device with good electrical performance.